Keadaan Sosial Masyarakat Pada Masa Pandemi Covid 19 Ditinjau Dari Kegiatan Keagamaan Umat Muslim Di Desa Wonosari Kec. Tanjung Morawa Kab. Deli Serdang - Alfani, Dela; Chairrani, Tengku; Rusdi Hidayat, Ahmad; Armia (Universitas Pangeran Diponegoro Nganjuk, 2025)
This study aims to explain the impact of the COVID-19 pandemic on the social condition of the community from a religious perspective for Muslims. Methods of Implementation This community service program uses the CBR Community Based Research method. The subjects in this study were all Muslim residents in Wonosari village, Tanjung Morawa district, Kab. Deli Serdang, the object of this research is the Perwiritan Group, and the Koran teacher in the village of Wonosari. Data collection techniques used are observation and interviews. The data analysis technique is qualitative descriptive analysis. Types and sources of data This type of research is descriptive qualitative. The results in this study are based on the results of research conducted in Wonosari village, Tanjung Morawa sub-district, Deli Serdang regency, it can be seen that during the COVID-19 pandemic, the state of the community from a religious perspective was very disturbed, and very limited, even some of them were completely stopped until now.